THE CORRELATION BETWEEN STUDENTS’ SMA NATIONAL ENGLISH EXAMINATION AND THEIR INTEGRATED INTENSIVE COURSE (IIC) SCORES AT THE ENGLISH DEPARTMENT OF UHO - Sari, Naila; Nurnia, Nurnia; Siam, Siam (Journal of Teaching of English, 2021)
This study researched the correlation between the students’ national English examination and their integrated intensive course (IIC) scores at English Department of Halu Oleo University academic year of 2016/2017. The national examination test determined the English score of students in senior high schools based on 3 language skills; reading, listening and writing, while IIC test determined the 4 language skills; reading, writing, speaking and listening as well as vocabulary and grammar. The difference of test score may raised score variations in which students who got good scores in national examination might got even worse score in IIC. Moreover, different types of tests, where some senior high schools that carry out national examination through paper based and some other through computer based test also may impact the result of the test. The researcher used product moment correlation to analysis the correlation both of the score. The result of hypothesis shows that there is a significant correlation between the students’ national English examination and their integrated intensive course (IIC) scores at English Department of Halu Oleo University academic year of 2016/2017. It was indicated by the result of analysis of r-product moment score (rxy = 0.309) which was higher than r-table = 0.199.